STRATEGI PEMERINTAH TIMOR LESTE MENDAFTARKAN TENUN TAISKE DALAM WARISAN BUDAYA TAKBENDA UNESCO - Pinto Gama, Jose Soares; Putri, Penny Kurnia; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This research aims to describe the strategy of the Goverment of Timor Leste inregistering Tais weavingin the list of UNESCO’s Intangible Cultural Heritage through its foreign policy using descriptive qualitative research methods. Timor Leste is a newlyi ndependent country,so there are still many shortscoming in the fields of education, economy, politcs, social, and culture that the government needs to collaborate with many countries in the world and with international organizations. The activity received encouragement from various international and local organizations to work together. Therefore, researchers use the framework of thinking about Goverment to Government as First Track Diplomacy and Intangible Cultural Heritage concepts in answering the research issue. The research found that Timor Leste had a national interests in the 2011-2030 development strategy plan. Keywords:Tais Tenun,Traditional Woven Fabric, Intangible Cultural Heritage,UNESCO,Timor Leste Strategy,Timor Leste Government,Track One Diplomacy